The feminization of quest-romance : radical departures - Heller, Dana A. (Dana Alice), 1959- (University of Texas Press, 1990)
Heller examines the quest-romance genre and contends that we are witnessing the genre's development as one of the most fundamental formal expressions of women's awakening to selfhood, mobility, and influence in both American culture and mythology.